What to Say When It Matters: Communication Skills to Address Implicit Bias Workshop - Bria McKenzie; Dhanya Mahesh; Elena Gupta; Phuong Pham; Adina Harri; Erin M. Knight; Bich T. N. Tran; Arvind Suresh; Maya Ellis; Nan Cochran; Alison Kapadia (MedEdPORTAL)
Introduction In academic medicine, learners, faculty, and staff commonly experience microaggressions, which have been linked to multiple negative outcomes (e.g., higher levels of depression, deteriorating well-being, increased anxiety, and feelings of isolation). Workshops teaching communication skills can reduce barriers in responding to microaggressions. Our workshops included students, faculty, and staff as both participants and cofacilitators. Methods Each 2-hour, in-person workshop began with a large-group didactic. Next, cofacilitators led skills practice responding to microaggressions. Small-group cofacilitators underwent standardized training. Student and faculty/staff participants were surveyed after each workshop. We conducted factorial analyses of variance comparing the main effects of time, role (student vs. staff/faculty), and prior knowledge, as well as the interaction effects between time and role and between time and prior knowledge. Results Fourteen workshops were conducted between 2022 and 2023. Students attended four of the workshops, and faculty/staff participated in 10. Participants reported greater knowledge (p < .001) and comfort (p < .001) identifying and responding to microaggressions after the workshop. The interactions between time and role and between time and prior knowledge on the dependent variables knowledge and comfort were significant (knowledge: p < .01; comfort: p < .05). Discussion Active learning workshops constitute an effective method for teaching communication skills to address implicit bias in academic medicine. Including students as cocreators allows for greater relevance for student participants and authenticity for the student experience. Future directions include examining data on cofacilitator experiences and comparing outcomes for students versus faculty/staff.